Knowledge, attitudes, and practices pertaining to cotton-bud usages and the complications related to their mi suse among outpatients in an ear, nose, and throat clinic - Maha Saleh Alrajhi; Bader Mohammed Alim; Sara Dokhayel Aldokhayel; Leena Mohammad Zeitouni; Layan Khalid Al Tawil; Farid A Alzahrani (Wolters Kluwer Medknow Publications, 2019)
Introduction: Cotton buds are small plastic rods with cotton-covered tips. They have been widely misused since their development. Objectives: This study aims to determine the prevalence of cotton bud usage and examine patients' attitudes toward their utilization. It also aims to investigate the complications associated with their misuse. Methodology: This cross-sectional observational study was conducted in King Abdulaziz University Hospital, on patients attending the ear, nose, and throat outpatient clinics between January and March 2018. Data were collected using paper-based questionnaires and analyzed using SPSS. Results: A total of 378 patients completed the survey. Most respondents (69.6%) confirmed that they had used cotton buds previously. However, only 18% of the respondents suffered ear canal complications associated with cotton bud use. Respondents reported ear wax impaction as the most common complication (41.2%), followed by ear pain (39.7%). The majority (63.2%) of the respondents stated that they had received at least one educational session warning them against improper cotton bud use. Almost half of the patients were unsure whether cotton buds could cause complications or not. The mean overall rating of the attitude of the patients toward using cotton buds resulted in a score of 12 out of 20, thereby denoting that these patients were slightly inclined toward using cotton buds. Furthermore, patients who reported having used cotton buds had significantly greater attitudes toward cotton bud usefulness (mean, 13.4; standard deviation, 2.8; P < 0.001). Conclusion: Overall, patients seem to have relatively insufficient knowledge and lax attitudes toward cotton bud usage and the complications related to their use. Further studies on a broader scale are warranted to evaluate the extent of cotton bud use.